The Association Between Screen Time and Outdoor Time on Adolescent Mental Health and Academic Performance: Evidence from Rural China - Wang H; Abbey C; Kennedy T; Feng E; Li R; Liu F; Zhu A; Shen S; Wadhavkar P; Rozelle S; Singh MK (Dove Medical Press, 2023)
Huan Wang,1 Cody Abbey,1 Thomas Kennedy,1 Erik Feng,1 Robin Li,1 Finley Liu,1 Annli Zhu,1 Sharon Shen,1 Prateek Wadhavkar,1 Scott Rozelle,1 Manpreet K Singh2 1Stanford Center on China's Economy and Institutions, Stanford University, Stanford, CA, USA; 2Stanford School of Medicine, Stanford University, Stanford, CA, USACorrespondence: Cody Abbey, Stanford Center on China's Economy and Institutions, Stanford University, Stanford, CA, USA, Tel +1 650-723-4581, Email cjabbey@stanford.eduPurpose: We examine how adolescent free time allocation-namely, screen time and outdoor time-is associated with mental health and academic performance in rural China.Methods: This paper used a large random sample of rural junior high school students in Ningxia (n = 20,375; age=13.22), with data collected from self-reported demographic questionnaires (to assess free time allocation), the Strengths and Difficulties Questionnaire (to assess mental health), and a standardized math test (to measure academic performance). We utilized a multivariate OLS regression model to examine associations between free time allocation and adolescent outcomes, controlling for individual and family characteristics.Results: Our sample's screen time and outdoor time both averaged around 1 hour. About 10% of the sample adolescents reported behavioral difficulties, while a similar percentage (11%) reported abnormal prosocial behaviors. Adolescents with higher levels of screen time (> 2 hours) were 3 percentage points more likely to have higher levels of behavioral difficulties (p< 0.001), indicating that excessive screen time was associated with worse mental health. Meanwhile, outdoor time was associated with better mental health, and positive correlations were observed at all levels of outdoor time (compared to no outdoor time, decreasing the likelihood of higher levels of behavioral difficulties by between 3 and 4 percentage points and of lower prosocial scores by between 6 and 8 percentage points; all p's< 0.001). For academic performance, average daily screen times of up to 1 hour and 1- 2 hours were both positively associated with standardized math scores (0.08 SD, p< 0.001; 0.07 SD, p< 0.01, respectively), whereas there were no significant associations between outdoor time and academic performance.Conclusion: Using a large sample size, this study was the first to examine the association between adolescent free time allocation with mental health and academic performance, providing initial insights into how rural Chinese adolescents can optimize their free time.Keywords: adolescent outcome, free time allocation, correlational analysis, developing countries